Factor VIII Levels are Associated with Ischemic Stroke, Stroke Subtypes and Neurological Worsening - Kuo, Chih-Yu; Lin, Chun-Hsien; Kuo, Ya-Wen; Huang, Yen-Chu; Hsu, Huan-Lin; Lin, Ya-Hui; Wu, Chih-Ying; Huang, Ying-Chih; Lee, Meng; Yang, Hsin-Ta; Hsu, Chia-Yu; Pan, Yi-Ting; et al. (Current Neurovascular Research, 2015)
The role played by hemostasis in the pathogenesis of ischemic stroke is still controversial. In the present study, we looked for a possible association of ischemic stroke with the high clotting activity of factor VIII (FVIII). The study population consisted of 116 patients with acute ischemic stroke who had been admitted between September 2013 and September 2014 to the Department of Neurology, Chiayi Chang Gung Memorial Hospital, and 76 control subjects with no history of stroke. FVIII levels were higher in stroke patients as compared to controls (127.5 ± 52.5 vs. 108.4 ± 49.0 IU/dL; P = 0.012). In a univariate risk analysis, FVIII at levels above 150 IU/dL was associated with an odds ratio (OR) for ischemic stroke of up to 2.55 (95% CI, 1.20–5.42, P = 0.013). In a multivariate analysis using a logistic regression model including age, hypertension, low density lipoprotein cholesterol level, estimated glomerular filtration rate, and high FVIII (< 150 IU/dL), high FVIII was still found to significantly add to the risk of ischemic stroke (OR = 3.26 with 95% CI, 1.38–7.68, P = 0.007). As for the stroke subtypes, mean FVIII level was significantly higher in patients with cardioembolic stroke than patients with noncardioembolic stroke (156.0 ± 51.5 IU/dL vs. 124.3 ± 51.9 IU/dL). High levels of FVIII were also associated significantly with neurological worsening (OR = 3.66 with 95% CI, 1.24–10.82, P = 0.019). A high plasma level of FVIII is a prevalent and independent risk factor for ischemic stroke and neurological worsening after acute stroke.
Keywords: Association